Effects of Lily Polysaccharide on Immune Function and Intestinal Flora in Immunosuppressed Mice - Hou, J.Q.; Hao, J.M.; Zhong, M.; Ren, J.W.; Xu, W.T.; He, X.Y. (Current topics in nutraceuticals research, 2024)
The major goal of this study was to explore the effect of lily polysaccharides on immune function and intestinal flora in immunosuppressed mice. The immunosuppressed mouse model was established by treating mice with cyclophosphamide orally for 3 days and measuring post-treatment changes in immunological indexes. Also, the distribution of intestinal flora was determined by 16S DNA sequence analysis of cecal DNA. Compared with the cyclophosphamide group, there was a significant increase in the body weight and thymus index and a decrease in the liver index. The hepatocyte morphology, liver plate, and hepatic sinus arrangement of mice in the high- and low-concentration lily polysaccharide groups were corrected to varying degrees, and the contents of IgA and IgG in the serum of mice in the low-concentration lily polysaccharide group and the positive control group increased significantly. The contents of tumor necrosis factor-α and interleukin-6 in the colon decreased, while the contents of interleukin-10 increased significantly. The levels of aspartate transaminase, alanine aminotransferase, and malondialdehyde in the liver decreased significantly, while that of superoxide dismutase increased significantly. Compared with the blank group, lily polysaccharide increases the intestinal flora of immunosuppressed mice, mainly by increasing the abundance of beneficial bacteria such as Muribaculaceae (previously known as S24-7), Bacteroides, and Butyrimionas and decreasing the harmful bacteria such as Prevotella, Dorea, and Adlercreutzia.